Peran Kepala Madrasah Dalam Penguatan Pengembangan Keprofesian Berkelanjutan (PKB) Kelompok Kerja Guru 016 Kecamatan Gringsing Kabupaten Batang - Musfuji’atun, Siti; Untung, Slamet; Rohman, Taufiqur (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
This study aims to analyze the implementation of the Continuing Professional Development (PKB) program in the Teacher Working Group 016, Gringsing District, Batang Regency in 2023; to analyze the role of the madrasah head in supporting the implementation of the Continuing Professional Development (CPD) program in Teacher Working Group 016, Gringsing District, Regency in 2023. This study uses qualitative research with a type of phenomenology. The research subjects were in four MI, namely MI Islamiyah Yosorejo 01, MI Islamiyah Yosorejo 02, MI Islamiyah Kebondalem 01, and MI Islamiyah Kebondalem 02. Data collection techniques used interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman model which consists of data condensation, data presentation, and data verification. The results of the research show that the Continuing Professional Development Program (CPD) in Teacher Working Group 016, Gringsing District, Batang Regency in 2023 consists of self-development programs, scientific publications, and innovative work programs which can be categorized as low. Some of the obstacles found included inflexible time, lack of knowledge, lack of outreach, lack of mentoring and guidance, etc.; The role of the madrasa head in supporting the implementation of the Continuing Professional Development (CPD) program in Teacher Working Group 016, Gringsing District, Batang Regency in 2023 includes the roles of educator, manager, administrator, supervisor, leader, innovator, and motivator.